Current status and conservation of Pistacia germplasm - Ozden-Tokatli, Y.; Akdemir, H.; Tilkat, E.; Onay, A. (Pergamon-Elsevier Science Ltd, 2010)
The genetic erosion of Pistacia germplasm has been highlighted in many reports. In order to emphasize this and to focus more attention on this subject, national and international (especially IPGRI and IFAR) institutions have initiated projects proposing to characterize, collect and conserve Pistacia germplasm. Therefore, this paper reviews recent research concerning conventional (in situ and ex situ) and unconventional biotechnological conservation strategies applied to the preservation of Pistacia germplasm. As regards conventional conservation, the majority of germplasm collections of Pistacia species are preserved on farms (in situ) and in seed and field genebanks (ex situ), as well as in the wild, where they are vulnerable to unexpected weather conditions and/or diseases. Hence, complementary successful unconventional in vitro methods (organogenesis, somatic embryogenesis and micrografting) and slow-growth storage conditions for medium-term preservation of Pistacia are presented together with the morphological and molecular studies carried out for the characterization of its species in this review. Moreover. special attention is additionally focused on cryopreservation (dehydration- and vitrification-based one-step freezing techniques) for the long-term preservation of Pistacia species. Possible basic principles concerning the establishment of a cryobank for the successful conservation of Pistacia germplasm are also discussed. (C) 2009 Elsevier Inc. All rights reserved.
Keywords: Cryopreservation; Molecular markers; In vitro studies; Slow-growth storage